PROFILE OF STORY PROBLEM SOLVING OF THE TANGENT LINE ON THE CIRCLE BY STUDENTS OF CLASS IX E SMPN 5 PALU - Indriyani, Indriyani; Hasbi, Muh.; Anggraini, Anggraini; Baharuddin, Baharuddin (JME (Journal of Mathematics Education), 2024)
Penyelesaian soal cerita oleh siswa perlu diprofilkan agar guru dapat mengetahui gambaran atau gambaran kemampuan siswa dalam menyelesaikan soal cerita. Penelitian ini bertujuan untuk memperoleh profil penyelesaian soal cerita garis singgung sekolah lingkaran oleh siswa kelas IX E SMPN 5 Palu. Jenis penelitian ini adalah penelitian deskriptif dengan pendekatan kualitatif. Data dikumpulkan melalui tes tertulis dan wawancara. Hasil penelitian ini menunjukkan bahwa subjek berkemampuan matematika tinggi (SH) mampu mengerjakan soal dengan benar sebagai langkah-langkah penyelesaian soal cerita. Kemudian hasil penyelesaian subjek berkemampuan matematika sedang (EZ) menunjukkan adanya penyelesaian yang belum selesai sehingga jawaban yang diperoleh salah. Kemudian hasil penyelesaian subjek berkemampuan matematika rendah (FR) menunjukkan tidak mampu menyelesaikan soal sebagaimana langkah-langkah penyelesaian soal cerita sehingga jawaban yang diperoleh salah.Â Berdasarkan hasil penelitian tersebut peneliti menarik kesimpulan bahwa profil penyelesaian soal cerita siswa berbeda-beda berdasarkan kemampuan matematika siswa.Â Completion of story problems by students needs to be profiled so that teachers can know the description or description of students' abilities in solving story problems. This study aims to obtain a profile of the completion of the circle tangent story problem by students of class IX E SMPN 5 Palu. This type of research is descriptive research with a qualitative approach. Data were collected through written tests and interviews. The results of this study showed that SH was able to do the problem correctly as the steps of solving the story problem. Then the results of EZ's solution show that there is an unfinished solution so that the answer obtained is wrong. Then the results of FR's completion showed that he was unable to solve the problem as the steps of solving the story problem so that the answer obtained was incorrect. Based on the results of this study, the researcher draws the conclusion that the profile of solving students' story problems varies based on students' mathematical abilities.